MEMBANDINGKAN FUNGSI ALAT SERPIH PADA PENEMUANNYA DI INDONESIA BAGIAN BARAT DAN BAGIAN TIMUR TAHUN 1930-1980 - Faniesa Ardianti Mahdiyar (Historiography: Journal of Indonesian History and Education, 2021)
Indonesia became part of the site of the spread of prehistoric culture, one of which was the distribution of tools that facilitated prehistoric human life. Shale tool is one of the simple tools of prehistoric human culture that in its distribution, shale tools became the dominant element and often became the main element. The purpose of this study to examine the characteristics of the discovery of shale tools in Western and Eastern Indonesia and compare the functions of the discovery of shale tools in Western and Eastern Indonesia. The research uses a methodological approach to history that includes four stages ranging from the heuristic stage, the criticism stage, the interpretation stage, and historiography. Through this study, it can be understood the comparison of the discovery of shale tools ranging from the characteristic aspects to aspects of prehistoric cultural functions in Indonesia, especially in Western and Eastern IndonesiaIndonesia menjadi bagian dari tapak tilas persebaran kebudayaan prasejarah, salah satunya persebaran perkakas-perkakas yang mempermudah kehidupan manusia prasejarah. Alat serpih merupakan salah satu perkakas sederhana hasil kebudayaan manusia prasejarah yang dalam persebarannya, alat serpih menjadi unsur dominan dan seringkali menjadi unsur pokok. Adapun tujuan dari penelitian ini untuk mengkaji mengenai karakteristik penemuan alat serpih di Indonesia bagian barat dan bagian timur serta membandingan fungsi dari penemuan alat serpih di Indonesia bagian barat dan timur. Penelitian menggunakan metodelogi pendekatan sejarah yang meliputi empat tahap mulai dari tahap heuristik, tahap kritik, tahap interpretasi, dan historiografi. Melalui kajian ini, dapat dipahami perbandingan penemuan alat serpih mulai dari aspek karakteristik sampai aspek fungsi kebudayaan prasejarah di Indonesia, khususnya di Indonesia bagian barat dan bagian timur.